Differences in lucid dream reports and non-lucid dream reports: a single-case analysis - Schredl, Michael (International journal of dream research, 2024)
Lucid dreams are dreams in which the dreamer is aware that s/he is dreaming. Skilled lucid dreamers often choose pleasurable activities like flying or having sex; thus, lucid dreams should be more bizarre and more positively toned than dreams in general. Although, some dream content analytic findings confirmed this, there also conflicting results. The present study analyzed all lucid dreams (47 pre-lucid, 34 lucid dreams without control, and 91 lucid dreams with control) recorded by a male dreamer over a time period of 32 years. As expected, the pre-lucid and lucid dreams showed more positive emotions and included more erotic and flying themes, but also less verbal interactions then the matched non-lucid control dreams. An exploratory analysis indicated that the three subgroups, pre-lucid dream, lucid dreams without control, and lucid dreams with control showed different patterns compared to the matched non-lucid dreams, e.g., the lucid dreams with control showed the highest bizarreness. Regarding emotions, only the lucid dreams with control showed a clear increase in positive emotions compared to non-lucid dreams, whereas only minor differences were found for pre-lucid dreams and lucid dreams without control. An important methodological advantage of the present study was that all pre-lucid and lucid dreams of the dreamer were included, and the non-lucid dreams were randomly selected; therefore, possible selection biases, e.g., reporting fun lucid dreams or bizarre non-lucid dreams were minimized. Thus, these findings - even though only based on a single participant - can help to elucidate the discrepancies reported in the literature dealing with dream content of lucid dreams.
Gesehen am 16.04.2024